1999
DOI: 10.1002/(sici)1098-2396(19990915)33:4<268::aid-syn3>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

GBR12909 attenuates amphetamine-induced striatal dopamine release as measured by [11C]raclopride continuous infusion PET scans

Abstract: Major neurochemical effects of methamphetamine include release of dopamine (DA), serotonin (5-HT), and norepinephrine (NE) via a carrier-mediated exchange mechanism. Preclinical research supports the hypothesis that elevations of mesolimbic DA mediate the addictive and reinforcing effects of methamphetamine and amphetamine. This hypothesis has not been adequately tested in humans. Previous in vivo rodent microdialysis demonstrated that the high affinity DA uptake inhibitor, GBR12909, attenuates cocaine- and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 25 publications
(25 reference statements)
1
25
0
Order By: Relevance
“…The lack of effect of the challenges on the nonspecific binding indicated that the change in V 3 00 was exclusively due to change in receptors availability to [ 11 C]raclopride binding. The data set also documented the (Laruelle et al, 1997;Villemagne et al, 1999). The effect of methamphetamine on [ 11 C]raclopride in vivo binding is also significantly blunted in patients with Parkinson's disease (Piccini et al, 2003).…”
Section: Discussionmentioning
confidence: 83%
“…The lack of effect of the challenges on the nonspecific binding indicated that the change in V 3 00 was exclusively due to change in receptors availability to [ 11 C]raclopride binding. The data set also documented the (Laruelle et al, 1997;Villemagne et al, 1999). The effect of methamphetamine on [ 11 C]raclopride in vivo binding is also significantly blunted in patients with Parkinson's disease (Piccini et al, 2003).…”
Section: Discussionmentioning
confidence: 83%
“…Imaging studies have corroborated the ability of oral MP to induce significant levels of DAT blockade in the striatum, with an estimated ED50 (dose required to block 50% of the DAT) of 0.25 mg/kg (Volkow et al, 1999a). Imaging studies have also shown that MP and AMP, at clinically relevant doses, can significantly increase extracellular DA (Villemagne et al, 1999;Volkow et al, 1999bVolkow et al, , 2009a. Imaging studies in non-human primates have also shown significant blockade of the NE transporter at doses that are pharmacologically equivalent to those used in humans, which is interesting in light of the data indicating that enhanced extracellular catecholamine levels in cortical regions, secondary to NE reuptake inhibition, improves multiple aspects of inhibitory control over responding in rats and monkeys (Seu et al, 2009).…”
Section: Pet Imaging Studies Of Adhd Adults and Effect Of Stimulant Dmentioning
confidence: 99%
“…DA releasers, such as amphetamine or methamphetamine, also bind to DAT and they enhance neurotransmitter release by reversing DA transport (Elliott and Beveridge, 2005;Sulzer et al, 2005). It has been shown that DA uptake blockers can also block reverse transport, thereby antagonizing the increase in extracellular DA induced by a DA releaser (Zetterstrom et al, 1988;Hurd and Ungerstedt, 1989;Villemagne et al, 1999;Baumann et al, 2002). Furthermore, DA uptake blockers and DA releasers exert differential effects on vesicular monoamine transporter-2 (VMAT-2) function, which seems to depend on a redistribution of VMAT-2 to different cellular compartments, and it has been suggested that the neurotoxic effects of amphetamines are related to their effects on VMAT-2 trafficking (Sandoval et al, 2003;Hanson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%